Management of Biliopleural Fistula after Transarterial Chemoembolization of a Liver Lesion - Amir Shahzad Butt; Ghulam Mujtaba; Sury Anand; Mahesh Krishnaiah (Canadian Journal of Gastroenterology)
A case of a biliopleural fistula with a biloma occurring after superselective hepatic transarterial chemoembolization ablation of a metastatic hepatic carcinoid is described. The presentation was complicated by choledocholithiasis. The biloma was successfully treated with endoscopic drainage.